Why do nurses miss infection control activities? A qualitative study. Issue 1 (February 2020) - Henderson, Julie; Willis, Eileen; Roderick, Allison; Bail, Kasia; Brideson, Genevieve
Abstract: Background: Hospital acquired infections (HAIs) increase length of hospital stay and lead to poorer clinical outcomes. HAIs are viewed as preventable through risk monitoring and prevention of transmission. These activities are frequently missed. This study explores missed infection control activities through the lens of missed or rationed care. Aim: To determine the factors that contribute to infection control activities being missed. Methods: Semi-structured interviews were conducted with eleven nurses with infection control expertise. Findings: Four major factors were identified as contributing to infection control activities being missed. These are systemic factors such as poor staffing and skillmix which contribute to time constraints and difficulties with identifying signs of infection; environmental factors such as ward layout and access to Personal Protective Equipment (PPE); organisational factors including lack of managerial support and interprofessional relationships; and personal factors, primarily the priority given to infection control by the nurse and knowledge, understanding and application of the principles of infection control. Discussion: Policy responses to HAI frequently focus upon surveillance and education however, resourcing, organisational and interprofessional support and hospital layout all contribute to infection control activities being missed. Conclusion: Further research is required into the impact of systemic factors upon infection control activities being missed.